KAJIAN KELUARGA DALAM UPAYA PENCEGAHAN PENYAKIT THALASSEMIA MAYOR DI INDONESIA : FAMILY STUDY IN THE EFFORT TO PREVENT THALASSEMIA MAJOR IN INDONESIA - Ain, Nurul (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Thalassemia and hemoglobinopathies are genetic disorders inherited in an autosomal recessive manner, with the risk of thalassemia major increasing if both parents are carriers. In Indonesia, the prevalence of thalassemia gene carriers reaches 3–10%, while hemoglobin E is a fairly common variant in Southeast Asia. This study aims to evaluate the genetic status of the parents of children with thalassemia major as a preventive measure through family screening and genetic counseling. This descriptive cross-sectional study was conducted on 35 parents at the Department of Clinical Pathology, Faculty of Medicine, University of North Sumatra / Adam Malik Hospital, Medan. Laboratory examinations included complete blood count, peripheral blood morphology, and hemoglobin electrophoresis. The results showed that 33 of 35 couples (94.1%) were carriers of β-thalassemia and/or heterozygous Hb E. This finding confirms that marriages between carriers have a high risk of giving birth to children with thalassemia major. Therefore, family screening and genetic counseling need to be the main strategies in preventing thalassemia major in Indonesia, especially in areas with high prevalence. This effort is expected to significantly reduce the incidence of thalassemia major through early detection and public education. AbstrakThalassemia dan hemoglobinopati adalah kelainan genetik yang diturunkan secara autosomal resesif, dengan risiko thalassemia mayor meningkat bila kedua orang tua merupakan pembawa sifat. Di Indonesia, prevalensi pembawa gen thalassemia mencapai 3–10%, sedangkan hemoglobin E merupakan varian yang cukup umum di Asia Tenggara. Penelitian ini bertujuan mengevaluasi status genetik pasangan orang tua dari anak penderita thalassemia mayor sebagai upaya pencegahan melalui skrining keluarga dan konseling genetik. Penelitian deskriptif cross-sectional ini dilakukan pada 35 pasangan orang tua di Departemen Patologi Klinik Fakultas Kedoktran Universitas Sumatera Utara / Rumah Sakit Adam Malik Medan. Pemeriksaan laboratorium meliputi hitung darah lengkap, morfologi darah tepi, dan elektroforesis hemoglobin. Hasil menunjukkan bahwa 33 dari 35 pasangan (94,1%) merupakan pembawa sifat thalassemia β dan/atau Hb E heterozigot. Temuan ini menegaskan bahwa perkawinan antar pembawa sifat memiliki risiko tinggi melahirkan anak dengan thalassemia mayor. Oleh karena itu, skrining keluarga dan konseling genetik perlu menjadi strategi utama dalam pencegahan thalassemia mayor di Indonesia, khususnya pada wilayah dengan prevalensi tinggi. Upaya ini diharapkan dapat menurunkan kejadian thalassemia mayor secara signifikan melalui deteksi dini dan edukasi masyarakat.